Two-Dimensional vs. Three-Dimensional FE Modeling of Skin and Proximity Effects in Segmented Cables with Parallel Conductors: A Comparative Study - Soheil Ahmadi; S. H. Khan; K. T. V. Grattan (Applied Sciences)
This paper investigates the influence of skin and proximity effects on power losses in segmented power cables using finite element (FE) analysis. Two-dimensional (2D) and three-dimensional (3D) FE models are developed to evaluate the AC-to-DC resistance ratio (<semantics>RAC/RDC</semantics>) in single-, three-, and five-segment cable configurations. Frequencies of 0, 50, 150, and 250 Hz are considered under an infinite lay length (parallel strands) assumption. This study reveals that 2D modeling provides nearly identical <semantics>RAC/RDC</semantics> values to 3D, with deviations of less than 0.6% at 50 Hz when no twisting is present. This highlights the computational efficiency of 2D models for certain cable designs without compromising accuracy. Furthermore, this paper examines the mesh refinement and sub-conductor geometry (hexagonal packing) of underground cables under full compression assumption. The results underscore the viability of 2D cross-sectional simulations for multi-segment cables, ensuring accurate loss predictions while saving considerable computational resources.